Новое состояние углерода: прозрачные нитевидные анизотропные кристаллы - Харламов, А.И.; Кириллова, Н.В.; Зайцева, З.А.; Смирнов, В.П.; Головкова, М.Е.; Алварез-Пуэбла, Р. (Видавничий дім "Академперіодика" НАН України, 2007)
For the first time, carbon as transparent thread-like anisotropic crystals is obtained. Their growth is carried out under reactionary conditions ensuring the generation of atoms of carbon (and also silicon) owing to the thermal evaporation (at temperatures higher than 1000 °С) of isotropic particles of carbon (and silicon). The transparent threads of carbon are formed in parallel with the formation of thread-like and tubular nanostructures of silicon carbide. The extremely original, inherent probably only in transparent carbon, morphology of the end of thread-like crystals (the macrothread end consists of a lot of microthreads) is revealed. The chemical composition of microthreads is determined by microanalyzers (Camebax-5X-50 and Superprobe-733) and by Raman spectroscopy with an ion — аrgon laser.